THE CAUSES OF HUMAN SMUGGLING(INDONESIA-MALAYSIA) AND THE POLICIES TAKEN BY THE INDONESIAN GOVERNMENT TO OVERCOME IT - Liu, Tiara Zulyansari (Journal of Social Political Sciences, 2024)
This research aims to analyze the causes of Human Smuggling experienced by Indonesian workers in Malaysia. The basic point of this research is the assumption that Indonesia, as a country that quantitatively contributes a very large number of labor exports (TKI) to other countries, at the same time on the "Tier 2 watch list", means there is a significant increase in human smuggling cases in Indonesia. The Human Smuggling cases that are of concern in this research are those that occur between Indonesia and Malaysia. The method used in this research is qualitative exploration, and the data collection used in this research is from journals, books, scientific reports, and others related to the research topic. The results consist of two things; first, human smuggling between Indonesia and Malaysia occurs due to the lack of education by migrant workers, which in turn affects the workers' mentality. In this aspect, the economic condition of workers is also an important cause of human smuggling. Second, legal politics in the aspect of migrant worker friendliness has not been maximized.